The Statute Law of the State of New York: Comprising the Revised Statutes and All Other Laws of General Interest, in Force January 1, 1881, Arranged Alphabetically According to Subjects, at 321, ch. 3, § 9 (Vol. 1, 1881) - (:unkn) unknown (General Publisher, 1881)
Prohibited using, attempting to use, or concealing a slungshot, billy, sandclub or metal knuckles, and any dirk. Punishable by imprisonment for up to 1 year and/or a fine up to $500.
--
Keywords: POSSESSION - NON-GUN ARMS